PENGARUH PENDAYAGUNAAN ZAKAT PRODUKTIF TERHADAP PEMBERDAYAAN MUSTAHIQ DI KOTA MEDAN - Siti Halida Utami; Irsyad Lubis (Departemen Ekonomi Pembangunan USU, 2014)
This research is aimed to determine the role of Badan Amil Zakat Nasional Sumatera Utara (BAZNAS SU), an official zakat institutions in North Sumatera owned by the government, in empowering mustahiq by the utilization of productive zakat and to analyze the influence of productive zakat fund toward mustahiq’s income. This research used descriptive method and Paired T-Test method in order to identify and to analyze data that obtained from the interviews based on the questionnaire. The result of Paired T-test shows that there is a difference between mustahiq’s income, before and after receiving the zakat productive’s fund. Descriptive analysis shows that BAZNAS SU distribute the zakat productive’s fund in the form of interest-free loans or revolving fund for small businesses, in order to empower the mustahiq. In addition to distributing zakat productive, BAZNAS SU also do supervision and guidance to mustahiq in using the zakat productive’s fund.Key Words : Badan Amil Zakat Sumatera Utara (BAZNAS SU), Zakat Productive, Empowerment of Mustahiq, Mustahiq’s Income.